The aspects of Total Quality Management in higher education institutions - Abdelnabi Salem, Milad; Shawtari, Fekri; Iqbal Hussain, Hafezali Bin; Shamsudin, Mohd Farid (Opción, 2019)
This study aims to identify the most important aspects of total quality management in the Community College of Qatar (CCQ) and attention paid by decision-makers to these aspects. The study adopted a quantitative approach using a self-reported questionnaire for collecting the data from both academician and administrative staff at CCQ (Critical Care Quarterly). The results revealed that TQM (Total Quality Management) at CCQ could be classified into four dimensions named quality management system recognition, stakeholders focus, leadership and vision, and measuring and continues improvement. In conclusion, the descriptive statistics of the data shows that these aspects have gained good attention from the management of CCQ.